1996
DOI: 10.1116/1.580094
|View full text |Cite
|
Sign up to set email alerts
|

Production and destruction of CFx radicals in radio-frequency fluorocarbon plasmas

Abstract: Spacially resolved densities of CF, CF 2 , and CF 3 radicals in capacitively coupled 13.56 MHz radio-frequency ͑rf͒ discharges in CF 4 and CHF 3 were determined by means of infrared absorption spectroscopy employing a tunable diode laser spectrometer. It was established that the stationary CF 2 density and density profile in a CF 4 plasma depend strongly on the electrode material. This is attributed to different sticking coefficients of CF 2 on different surfaces. Furthermore, it was found that the densities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…[5,6] Small reactive intermediates, such as CF 2 , play important roles in determining the etching rate, selectivity and anisotropy of plasma-etching processes. The mechanisms of CF 2 production and destruction in fluorocarbon reactive ionetching processes have been investigated using techniques such as laser induced fluorescence, [11] broad-band UV absorption spectroscopy, [12,13] infrared diode laser spectroscopy [14,15] and cavity-ring down spectroscopy. [16] It has been found that the primary mechanism for CF x production (where x = 1, 2 and 3) is neutralisation and fragmentation of CF x + (x = 1-4) ions incident on the powered electrode and not direct electron-impact induced fragmentation of the feedstock gas.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Small reactive intermediates, such as CF 2 , play important roles in determining the etching rate, selectivity and anisotropy of plasma-etching processes. The mechanisms of CF 2 production and destruction in fluorocarbon reactive ionetching processes have been investigated using techniques such as laser induced fluorescence, [11] broad-band UV absorption spectroscopy, [12,13] infrared diode laser spectroscopy [14,15] and cavity-ring down spectroscopy. [16] It has been found that the primary mechanism for CF x production (where x = 1, 2 and 3) is neutralisation and fragmentation of CF x + (x = 1-4) ions incident on the powered electrode and not direct electron-impact induced fragmentation of the feedstock gas.…”
Section: Introductionmentioning
confidence: 99%
“…On this reason we allowed dependences rcF2(TW) for one pressure but different discharge ourselves to discuss a little the possible loss currents. Solid lines are linear fits of data by using the expression mechanism of CF2 and CF on a fluorocarbon (11) (see text). surface by using the results of both our and other works.…”
Section: Losses Of Cf2 and Cf Radicals On A Surfacementioning
confidence: 99%
“…It is reasonable that researches of CF4 plasma attract so particular interest [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. No wonder that many electrodynamic models of CF4 plasma with using different sets of electron scattering cross-sections on CF4 molecules exist now [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, from this point of view, the seasoning procedure is also important. Here we report on wall heating and seasoning procedure as ways of controlling the chamber wall [11,12].…”
Section: Control Of Chamber Wallmentioning
confidence: 99%